Factors related to poor practice of pap smear screening among secondary school teachers in Malaysia - Abdullah, Fauziah; Aziz, Norlaili Abdul; Tin, Tin Su (West Asia Organization for Cancer Prevention, 2011)
Introduction: The Pap smear test has been regarded as a promising cervical screening tool since 1940s. Yet its importance has been overlooked by beneficiaries in Malaysia. This underlines the need to identify the prevalence of Pap smear practice and influencing factors towards the practice among educated working women. Methods: A survey was conducted with 403 female teachers from 40 public secondary schools in Malaysia selected by cluster random sampling. Data were collected from January to March 2010 using a self-administered questionnaire. Multivariate logistic regression was performed to identify the factors related to the Pap smear practice. Results: The rate for participants who ever had Pap test was only 38 and poor practice of was significantly higher among: those with aged less than 35 years; those practicing hormonal contraceptive method; and individuals perceiving barriers to the Pap smear screening test. In contrast, the findings were significantly lower in women with longer duration of teaching service; higher income groups; ever pregnant; having chronic diseases; health insurance coverage; and who had perceived benefit of Pap smear screening. Conclusion: Barriers towards practicing Pap smear exist even among educated career women. Tailor-made health promotion and education on cervical cancer and the benefit of Pap smear screening are essential to change the behavior of the study population.